Generalized inverse and it’s applications to the solutions of system of linear equations and semigroup - Shiham, Muhtadi Nasrullah (BRAC University, 2018)
This thesis is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Science in Mathematics 2018.